Splošni večdimenzijski vprašalniki za merjenje kakovosti življenja - Rifel, Janez (Medicinski razgledi, 2006)
One of the essential elements of healthcare evaluation is the assessment of health-related quality of life. Health-related quality of life refers to how health impacts an individual's ability to function and his or her perceived well-being in physical, mental and social domains of life. A range of generic health status measures are currently available and each of these measures has its particular strengths and weaknesses. The decision to use any one in a particular survey or clinical trial, or as a tool in clinical practice is often based on diverse scientific and extrascientific considerations. None of the instruments performs uniformly as best or worst. In this review, conceptual and measurement models of 9 generic multi-dimensional health statusmeasures are presented: the Medical Outcomes Study 36-item and 12-item Short Form Health Survey, the Nottingham Health Profile, the WONCA/COOP charts, the DUKE Health Profile, the EQ-5D, the Sickness Impact Profile, the Quality of Well-Being Scale and the Health Utilities Index.
Keywords: ankete; Quality Of Life; Health Status; Kvaliteta življenja; Questionnaires; Zdravstveno stanje; zdravje; vprašalniki